Qualidade do serviço público odontológico no Brasil: a percepção de usuários e profissionais da saúde - Bordin, Danielle [UNESP] (2014)
Studies aimed at understanding the different dimensions involved in the perception of users and health professionals allow wider and reliable regarding the current health assessment model. The aim of this study is to analyze user' satisfaction with the Brazilian public dental services, in its different dimensions of care and relate them to the socioeconomic and demographic conditions; and analyze the prediction of professionals about the satisfaction of users. It is a cross-sectional survey, quantitative, developed in the city of Ponta Grossa, Paraná. Study participants: 461 users, 30 dentists (CD), 22 technicians/assistants oral health (TSB/ASB) and 133 community health workers (ACS). It was used interview with structured questionnaire. The user profile was associated with overall satisfaction with the chi-square test. The questions were evaluated individually and grouped into domains. To analyze an index from 0 to 1 was created valuing the answers: satisfied (value 1), more or less (value 0,5) and dissatisfied (value 0) and applied the Kruskal-WallisTest with Dunn's post-test. Users showed that were satisfied in relation to public dental services (0.80). Elderly users, with low education and male, tended to evaluate more positively the services (p<0.05). The users added more satisfaction to the 'physical structure' (0.90) and 'relation and communication' (0.85) domain. The domain 'organization of services' was the one that received the worst rating among all classes of the subjects interviewed. The CD and TSB/ASB have exposed greater satisfaction than revealed by users in the most of the variables evaluated, however, no statistically significant difference (p>0.05). The ACS have exposed a vision that users would be less than pleased to be demonstrated, significant difference for: overall satisfaction (p<0.05); 'quality of clinical care' (p<0.001); 'orientation to the patient...